Implementation of The Principal's Flagship Program in Increasing Enrollment at Muhammadiyah 1 Junior High School in Surakarta - Nabila Febianza Arvi; Mohammad Zakki Azani (FKIP - Universitas Riau, 2026)
This study aims to describe the managerial strategies of the Principal of SMP Muhammadiyah 1 Surakarta in efforts to improve the quality of education while also increasing public interest in the New Student Admission (PPDB) process. The research employs a descriptive qualitative method with data collected through interviews and documentation. The findings show that the principal implements a visionary leadership style and engages the participation of the entire school community through programs such as Among Siswa Plus, Breaking News, PRESISI (Simpon Student Attendance) and Teacher Fingerprint System, ICT Classes, Character and Morality Report Cards, Simpon Mart and Food Court, and the Integrity Pact, all executed intelligently, sincerely, and optimally. These programs enhance teacher professionalism, foster a religious–collaborative culture, and create a modern, technology-based learning environment. Consistent implementation of these strategies has resulted in increased public trust, higher enrollment numbers, improved student achievement, and greater external recognition for the school. Overall, the school’s success is the result of synergy between leadership, innovation, technology, and the commitment of the entire school community.